1994
DOI: 10.1161/01.cir.90.5.2315
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death in the young. Is acute coronary thrombosis the major precipitating factor?

Abstract: In our study population, sudden death was precipitated by acute coronary thrombosis in only 27% of patients with obstructive coronary atherosclerotic plaque. Most of the young victims of sudden death with obstructive coronary atherosclerosis showed single-vessel disease that affected the left anterior descending coronary artery and was due to fibrous plaques with neointimal smooth muscle cell hyperplasia and a preserved tunica media in the absence of acute thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(48 citation statements)
references
References 50 publications
5
41
1
1
Order By: Relevance
“…17 However, the prevalence of coronary artery disease increases with age, and this condition is the most frequent underlying cause in patients Ͼ30 years of age. 17,18 If parental history of coronary heart disease is a well-known risk factor for coronary heart disease, 12,13 we were unable to find any study that reported data on parental history of sudden death as a specific risk factor for sudden death.…”
Section: Possible Etiologic Pathwaysmentioning
confidence: 94%
“…17 However, the prevalence of coronary artery disease increases with age, and this condition is the most frequent underlying cause in patients Ͼ30 years of age. 17,18 If parental history of coronary heart disease is a well-known risk factor for coronary heart disease, 12,13 we were unable to find any study that reported data on parental history of sudden death as a specific risk factor for sudden death.…”
Section: Possible Etiologic Pathwaysmentioning
confidence: 94%
“…26 The observations noted above illustrate the problems encountered in attempting to predict acute coronary syndromes on the basis of histopathology of atherosclerotic plaques. Furthermore, the pathology of acute coronary syndromes cannot be reduced to the analysis of a localized unstable plaque.…”
Section: Schmermund and Erbelmentioning
confidence: 98%
“…17,19,20,22,23,25,26 In Italy, ARVC and premature atherosclerotic coronary artery disease predominate. 24,30,39,40 On the basis of data from the United States, GCVDs account for at least 40% of sudden deaths in young athletes. 17,19,25 Many patients with these conditions aspire to participate in a variety of recreational sporting activities, and some may have even been previously withdrawn from competitive sports in accordance with the recommendations of Bethesda Conference No.…”
Section: Scope Of the Problemmentioning
confidence: 99%